1978
DOI: 10.1111/j.1540-4781.1978.tb02395.x
|View full text |Cite
|
Sign up to set email alerts
|

Errors of English Speakers of German As Perceived and Evaluated by German Natives

Abstract: negative or positive effects of correcting these errors may vary with the readiness of the learner to assimilate and apply the information provided in the correction. Little is known, however, about the nature of learners' interim grammars or the processes of fossilization.Finally, techniques and procedures need to be designed and tested for giving students feedback about the effects of their errors on communication. If the teacher's role in developing speaking proficiency in learners is to set optimal conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
2

Year Published

1983
1983
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 0 publications
0
25
0
2
Order By: Relevance
“…Examples ofsome ofthe questions investigated are the relationship between factors in the speakers' backgrounds and judgments of pronunciation accuracy (Suter, 1976;Purcell & Suter, 1980;Thompson, 1991), the comprehensibility of different types of accents (Smith & Bisazza, 1982), and the relationship between stereotypical reactions and the type of accent (Lambert, Hodson, Gardner, & Fillenbaum, 1960;Anisfeld, Bogo, & Lambert, 1962;Bradford, Farrar, & Bradford, 1974;Brennan, Ryan, & Dawson, 1975;Ryan & Carranza, 1975;Ryan, Carranza, & Moffie, 1977;Brennan & Brennan, 1981). Other studies investigating native speaker reactions to nonnative speech have investigated the effects of the subsystems of language (e.g., grammar and phonology) on native speakers' judgments (Politzer, 1978;Varonis & Gass, 1982), the effects of familiarity on comprehensibility (Gass & Varonis, 1984), and the effects of speaking rate on native speakers' comprehension of nonnative speech (Anderson-Hsieh & Koehler, 1988).…”
mentioning
confidence: 99%
“…Examples ofsome ofthe questions investigated are the relationship between factors in the speakers' backgrounds and judgments of pronunciation accuracy (Suter, 1976;Purcell & Suter, 1980;Thompson, 1991), the comprehensibility of different types of accents (Smith & Bisazza, 1982), and the relationship between stereotypical reactions and the type of accent (Lambert, Hodson, Gardner, & Fillenbaum, 1960;Anisfeld, Bogo, & Lambert, 1962;Bradford, Farrar, & Bradford, 1974;Brennan, Ryan, & Dawson, 1975;Ryan & Carranza, 1975;Ryan, Carranza, & Moffie, 1977;Brennan & Brennan, 1981). Other studies investigating native speaker reactions to nonnative speech have investigated the effects of the subsystems of language (e.g., grammar and phonology) on native speakers' judgments (Politzer, 1978;Varonis & Gass, 1982), the effects of familiarity on comprehensibility (Gass & Varonis, 1984), and the effects of speaking rate on native speakers' comprehension of nonnative speech (Anderson-Hsieh & Koehler, 1988).…”
mentioning
confidence: 99%
“…Of all errors type, vocabulary errors are the most serious one for the learners (Politzer, 1978). Additionally, large corpora of errors consistently introduced lexical errors as the most common error among second language learners.…”
Section: Resultsmentioning
confidence: 99%
“…Several confounding variables complicate learners' efforts to ascertain norms of NS expectations. They include contradictory views across and within NSs, such as reported in Dubiner et al (2006) and evidenced in the contradictory results of error-gravity studies for German (DeLisle 1982;Politzer 1978), the differential between the idealized standard language taught in foreign language classrooms and the real-life national and regional variants that, in turn, are bound by subtle social norms (e.g. Crispim 2000; Luzon, Campoy, del Mar Sanchez and Salazar 2007;Bieswanger 2008;Van Compernolle and Williams 2011), and the fact that communicative language teaching, the prevalent method of foreign language instruction in the US, has refrained from taking a firm ideological stance on accuracy, leaving matters of focus on form contested in both teaching practice and research (e.g.…”
Section: Experiential Deprivation In the Language Classroommentioning
confidence: 97%
“…Lindemann (2005), for example, demonstrated that biases held about specific ethnic and national groups affect how native speakers react differently to NNSs of English with different L1s. NS judgments may also vary by age group (Politzer 1978;DeLisle 1982) and schooling and gender (Politzer 1978).…”
Section: L1 Influence On Beliefs About Accuracymentioning
confidence: 99%